The association between severe menopausal symptoms and engagement with HIV care and treatment in women living with HIV. Issue 1 (2nd January 2021) - Solomon, Danielle; Sabin, Caroline A.; Burns, Fiona; Gilson, Richard; Allan, Sris; de Ruiter, Annamiek; Dhairyawan, Rageshri; Fox, Julie; Gilleece, Yvonne; Jones, Rachael; Post, Frank; Reeves, Iain; et al.
ABSTRACT: Using data from the PRIME Study, an observational study of the menopause in women living with HIV in England, we explored the association between menopausal symptoms and: (i) antiretroviral therapy (ART) adherence and (ii) HIV clinic attendance. We measured menopausal symptom severity with the Menopause Rating Scale (MRS, score ≥17 indicating severe symptoms), adherence with the CPCRA Antiretroviral Medication Adherence Self-Report Form, and ascertained HIV clinic attendance via self-report. Odds ratios were obtained using logistic regression. Women who reported severe menopausal symptoms had greater odds of suboptimal ART adherence (adjusted odds ratio (AOR) 2.22; 95% CI 1.13, 4.35) and suboptimal clinic attendance (AOR 1.52; 95% CI 1.01, 2.29). When psychological, somatic and urogenital domains of the MRS were analysed individually there was no association between adherence and severe symptoms (all p  > 0.1), however there was an association between suboptimal HIV clinic attendance and severe somatic (AOR 1.98; 95% CI 1.24, 3.16) and psychological (AOR 1.76; 95% CI 1.17, 2.65) symptoms. Severe menopausal symptoms were significantly associated with sub-optimal ART adherence and HIV clinic attendance, however we cannot infer causality, highlighting the need for longitudinal data.